Knowledge Fusion Patterns for Design of Context-Aware Decision Support Systems - Alexander Smirnov; Tatiana Levashova (Complex Systems Informatics and Modeling Quarterly)
The objective of the research is to offer a methodology providing a feasible functionality of context-aware systems for the users. The systems are considered consisting of a set of knowledge sources. These sources are involved in knowledge fusion processes to support the systems functionalities. The core of the methodology is knowledge fusion patterns. They characterize knowledge sources involved in the knowledge fusion processes in terms of preservation/change of the sources' autonomies and structures. In the methodology, the patterns are used to specify the requirements to the knowledge sources from the systems to ensure the full systems functionalities. Matching the system's requirements against the user's requirements to the system functionality and the user's constraints on the sources of information and knowledge enables to offer feasible system functionality to the users.